Mr. Magoo [videorecording (DVD)] : the theatrical collection, 1949-1959. - Kinney, Jack (Shout! Factory, 2014)
Collection of fifty-three theatrical shorts and the film "1001 Arabian nights" featuring the adventures of a near-sighted old man.